Cerebrospinal fluid analysis in the context of CNS demyelinating diseases - Matas,Sandro Luiz de Andrade (2013)
The central nervous system demyelinating diseases are a group of disorders with different etiologies, characterized by inflammatory lesions that are associated with loss of myelin and eventually axonal damage. In this group the most studied ones are multiple sclerosis (MS), neuromyelitis optic (NMO) and acute disseminated encephalomyelitis (ADEM). The cerebrospinal fluid is essential to differentiate between these different syndromes and to define multiple sclerosis, helping to assess the probability of Clinical Isolated Syndrome turn into multiple sclerosis.